HUBUNGAN SAINS DAN AGAMA DALAM PERSPEKTIF PARADIGMA SPIRAL ANDROMEDA UIN SUSKA RIAU DAN RODA WAHYU MEMANDU ILMU UIN SUNAN GUNUNG DJATI BANDUNG - Yusrianto, Edi; Arbi, Arbi; Syahrizul, Syahrizul (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the relationship between science and religion through two main paradigms, namely the Andromeda Spiral Paradigm from UIN Suska Riau and the Wheel of Revelation Guiding Science Paradigm from UIN Sunan Gunung Djati Bandung. This study was conducted to meet the need for integrative understanding that combines science and spiritual values in facing the challenges of a complex era. The method used is descriptive qualitative with data collection techniques through documentation studies, literature reviews, and analysis of relevant cases related to the application of both paradigms. Data analysis was carried out interpretively and comparatively to understand how these paradigms integrate science and religion within the framework of Islamic science. The results of the study show that both paradigms have succeeded in building a holistic conceptual framework, where science and religion are positioned as two complementary aspects, not contradictory. The Andromeda Spiral Paradigm emphasizes the development of knowledge continuously and dynamically, while the Wheel of Revelation Paradigm emphasizes the importance of revelation as the center of guiding science. Both together form a strong integration model between intellectual and spiritual aspects in Islamic education. In conclusion, the Andromeda Spiral and Wheel of Revelation paradigms can be used as a basis for developing an integrative scientific approach in Islamic universities. Further research is needed to examine the practical implementation of these two paradigms in curriculum development and cross-disciplinary studies to strengthen the synergy between science and religion in the academic environment.